2007
DOI: 10.1093/ageing/afm128
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of dementia in the People's Republic of China: a systematic analysis of 1980–2004 studies

Abstract: Background dementia has been a major public health problem. However, there has not yet been a nationwide investigation or systematic analysis of the prevalence of dementia in China from 1980 to 2004. Objectives the aim of this study was to analyse the prevalence of dementia and its major subtypes [Alzheimer disease (AD), vascular dementia (VD)] among the population aged 60 years and older in China from 1980 to 2004. Methods epidemiological investigations on dementia in China published in journals and covering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(87 citation statements)
references
References 13 publications
9
75
0
3
Order By: Relevance
“…There was previously just one prevalence study available from Latin America (13). The evidence base from China was considerably extended by a recent systematic review that included data from publications previously available only in Chinese journals (35). The previous estimates for South Asia were perhaps disproportionately influenced by one large study, from rural Ballabgarh in northern India, which recorded an unusually low prevalence (18).…”
Section: Discussion -Prevalence Of Dementiamentioning
confidence: 99%
“…There was previously just one prevalence study available from Latin America (13). The evidence base from China was considerably extended by a recent systematic review that included data from publications previously available only in Chinese journals (35). The previous estimates for South Asia were perhaps disproportionately influenced by one large study, from rural Ballabgarh in northern India, which recorded an unusually low prevalence (18).…”
Section: Discussion -Prevalence Of Dementiamentioning
confidence: 99%
“…4 Cities Study reported some variations between different cities and 4 Provinces Study found significantly higher risk of dementia in rural than in urban areas. A preliminary result of a recent study in mainland China also reported higher prevalence in rural areas.…”
Section: Implications For Future Discipline Studiesmentioning
confidence: 98%
“…In the immediate and mid term future, investigating the nationwide prevalence of dementia and the distributions in different areas are both important in providing information for appropriate policy and care plans. Some large scale exercises which synthesise Chinese data on dementia do exist but none of them consider the influence of methodological factors on the results [2][3][4][5]. An international Lancet report (Delphi study) seven years ago concluded the consensus prevalence of dementia in China and the developing western Pacific as 4.0% in those aged over 60 years [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Rusanen et al [29] inand amplifies the cholinergic metabolism by dysfunctioning brain nicotine receptacles. A Chinese research [30] proved that second-hand smoking constitutes a risk factor which could increase by 29% the occurrence of severe dementia.…”
Section: Factors Associated With Dementiamentioning
confidence: 99%